Hubungan antara Gratitude dengan Subjective Well-being Guru Honorer Sekolah Luar Biasa (SLB) di Kecamatan Koto Tangah Kota Padang - Utami, Mayumi Emphaty; Pratama, Mario (Lembaga Yasin AlSys, 2024)
This study aims to explore the connection between gratitude and subjective well-being among honorary special school teachers in Koto Tangah District, Padang City. Special education plays a crucial role in supporting the development of children with special needs, where special school teachers significantly contribute to their educational progress. Many challenges faced by honorary teachers, including an income that does not align with their workload, often lead to stress and fatigue, affecting their subjective well-being. Gratitude is one factor that may positively influence subjective well-being. The study employs a quantitative approach with a correlational design, using a sample of 50 honorary teachers selected through purposive sampling. Data were collected using a Likert scale and analyzed with the Pearson product-moment correlation test. The findings indicate that: a) the average level of gratitude among honorary special school teachers falls within the low category (42%), followed by moderate (40%) and high categories (18%); b) the average level of subjective well-being among honorary special school teachers is also low (62%), followed by moderate (34%) and high (4%); and c) the correlation analysis shows a Pearson coefficient of 0.740 with a significance level of 0.000 < 0.05, demonstrating a positive and significant relationship between gratitude and subjective well-being. The results suggest that a higher level of gratitude correlates with higher subjective well-being among teachers.